Innovation Through Tradition: The Role of Past Knowledge for Successful Innovations in Family and Non-family Firms. (March 2023) - Gusenbauer, Michael; Schweiger, Nina; Matzler, Kurt; Hautz, Julia
Innovation literature increasingly considers the importance of the temporal dimension of knowledge search. In particular, several qualitative studies demonstrate how family firms successfully search for and recombine mature knowledge into innovations. This paper extends this line of research by quantitatively examining knowledge search in family versus non-family firms in a unique dataset in global wine technology between 1956 and 2013. Our data show that family firms use mature knowledge in their innovation processes to a greater extent than non-family firms. Furthermore, family firms seem to draw higher value from mature knowledge than non-family firms.